Nitrogen Fertilizer Deep Placement for Increased Grain Yield and Nitrogen Recovery Efficiency in Rice Grown in Subtropical China - Wu, Meng; Li, Guilong; Li, Weitao; Liu, Jia; Liu, Ming; Jiang, Chunyu; Li, Zhongpei (Frontiers in Plant Science, 2017)
Field plot experiments were conducted over three years (from April 2014 to November 2016) in a double-rice (Oryza sativa L.) cropping system in subtropical China to evaluate the effects of N fertilizer placement on grain yield and N recovery efficiency. Different N application methods included: no N application (CK); N broadcast application (NBP); N and NPK deep placement (NDP and NPKDP, respectively). Results showed that grain yield and apparent N recovery efficiency significantly increased for NDP and NPKDP as compared to NBP. The main reason was that N deep placement increased the number of productive panicle per m−2 (PPN). To further evaluate the increase, a pot experiment was conducted to understand the N supply in different soil layers in NDP during the whole rice growing stage and a 15N tracing technique was used in a field experiment to investigate the fate of urea-15N in the rice–soil system during rice growth and at maturity. The pot experiment indicated that N deep placement could maintain a higher N supply in deep soil layers than N broadcast for 52 days during rice growth. The 15N tracing study showed that N deep placement could maintain much higher fertilizer N in the 5–20 cm soil layer during rice growth and could induce plant to absorb more N from fertilizer and soil than NBP, which led to higher N recovery efficiency. One important finding was that NDP and NPKDP significantly increased fertilizer N recovery efficiency but did not lead to N declined in soil compared to NBP. Compared to NPK, NPKDP induced rice plants to absorb more fertilizer N rather than soil N.